2023
DOI: 10.3390/v15040962
|View full text |Cite
|
Sign up to set email alerts
|

Revision of Cytomegalovirus Immunoglobulin M Antibody Titer Cutoff in a Maternal Antibody Screening Program in Japan: A Cohort Comparison Involving a Total of 32,000 Pregnant Women

Abstract: Cytomegalovirus (CMV) is associated with congenital infections. We aimed to validate the revised CMV immunoglobulin (Ig) M titer cutoff for IgG avidity measurements as a reflex test in maternal screening to identify women with primary CMV infection and newborn congenital cytomegalovirus (cCMV). We screened maternal CMV antibodies (the Denka assay) in Japan, from 2017 to 2019, using a revised IgM cutoff (≥4.00 index). Participants were tested for IgG and IgM antibodies, and for IgG avidity if IgM levels exceede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Fetal congenital cytomegalovirus (cCMV) infection occurs due to transplacental CMV transmission. According to a large study in Japan, the CMV antibody prevalence among pregnant women was 64.2% [ 1 ]. Alternatively, another large study in Japan reported that the incidence rate of neonatal cCMV infection was 0.3% [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fetal congenital cytomegalovirus (cCMV) infection occurs due to transplacental CMV transmission. According to a large study in Japan, the CMV antibody prevalence among pregnant women was 64.2% [ 1 ]. Alternatively, another large study in Japan reported that the incidence rate of neonatal cCMV infection was 0.3% [ 2 ].…”
Section: Introductionmentioning
confidence: 99%